Serum albumin to globulin ratio is related to cognitive decline via reflection of homeostasis: a nested case-control study. Issue 1 (December 2016) - Koyama, Teruhide; Kuriyama, Nagato; Ozaki, Etsuko; Matsui, Daisuke; Watanabe, Isao; Miyatani, Fumitaro; Kondo, Masaki; Tamura, Aiko; Kasai, Takashi; Ohshima, Yoichi; Yoshida, Tomokatsu; Tokuda, Takahiko; et al.
Abstract Background Recent research suggests that several pathogenetic factors, including aging, genetics, inflammation, dyslipidemia, diabetes, and infectious diseases, influence cognitive decline (CD) risk. However, no definitive candidate causes have been identified. The present study evaluated whether certain serum parameters predict CD. Methods A total of 151 participants were assessed for CD using the Mini-Mental State Examination (MMSE), and 34 participants were identified as showing CD. Results Among CD predictive risk factors, Helicobacter pylori seropositivity was significantly predictive of CD risk, more so than classical risk factors, including white matter lesions and arterial stiffness [adjusted odds ratio (OR) = 4.786, 95% confidence interval (CI) = 1.710–13.39]. A multivariate analysis indicated that the albumin to globulin (A/G) ratio was the only factor that significantly lowered CD risk (OR = 0.092, 95% CI = 0.010–0.887). A/G ratio also was positively correlated with MMSE scores and negatively correlated with disruption of homeostatic factors (i.e., non-high-density lipoprotein, hemoglobin A1c, and high-sensitive C-reactive protein). Conclusions The current study results suggest that the A/G ratio is related to cognitive decline and may reflect homeostatic alterations.